An Nasawiyyah Fi Riwayat Zinah Li Nawal Al Sa’dawi - Merdu Arika (Arabic Education Program IAIN Pekalongan, 2017)
Literature have widely described the women existence and inequality. Feminist literary criticism is a study which focuses on analysis of women demanding justice of their existence. It also describes the elements of inequality occurred in